Integrasi Nilai Qur’ani dan Agenda SDGS : Solusi Islam Atas Krisis Lingkungan - Isfahani, A’yun; A’yun Isfahani; Mohamad Zaenal Arifin (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2025)
The current environmental crisis has become a global issue demanding serious attention from all of humanity. Phenomena such as global warming, pollution, deforestation, and the loss of biodiversity are largely the result of unsustainable and exploitative human activities. In response to this situation, the United Nations formulated the Sustainable Development Goals (SDGs), a global agenda comprising 17 goals and 169 targets that aim to achieve sustainable development across social, economic, and environmental dimensions. In parallel, Islam, through the Qur'an, has long offered ecological values that remain relevant today, such as the concept of humans as khalīfah (stewards of the Earth) in Surah Al-Baqarah [2]: 30, the prohibition of spreading corruption (fasād) in Surah Al-Baqarah [2]: 11, and the call for balance and avoidance of excess (isrāf) in Surah Al-Mā’idah [5]: 32. These principles reflect the spiritual and ethical responsibility of humankind in preserving the environment. This paper aims to explore and integrate Qur’anic ecological values with the SDGs agenda as a conceptual and practical contribution to addressing the global ecological crisis. The study employs a qualitative-descriptive method based on library research, analyzing relevant Qur’anic verses and official SDG documents. The discussion is divided into two main sections: Ecological values in the Qur’an and Integration of Qur’anic values with the SDGs framework. The findings indicate that Qur’anic teachings offer significant ethical and spiritual reinforcement to the broader vision of sustainable development.